(3fbO GdQLGds - (3GdJaQjTj, eUWai Hf GdMSjf GdMSjfj, J HYO (B1030(3gs ((3fGUQ Hf LeGR GdMSjfjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg NGdb Gddjd hGdfgGQ (B... (3HGH GdgeRI, BOe Hf ESMGb Hf YHO Gddg Hf SYO GdCSYQj, bej KbI dg cJGH jQhjg Yf eMeO Hf YHO GdLHGQs
(3BNQgG (B:s
(3BNQgG(B: (3hHgPG GdESfGO Yf GdTjNjf GdCLdjf, GdTjN aNQ GdOjf hGdSjO YejO GdOjf GdTjN GdEeGe GdYdGeI LeGd GdOjf GdMSf Hf jhSa GdeWgQ GdMdj(B. (3hGdMeO ddg hMOgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B24: 167s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJGQjNs